2011
DOI: 10.1007/s13592-011-0091-z
|View full text |Cite
|
Sign up to set email alerts
|

Nesting biology of two species of Megachile (Moureapis) (Hymenoptera: Megachilidae) in a semideciduous forest reserve in southeastern Brazil

Abstract: -Nests of Megachile (Moureapis) benigna and Megachile (Moureapis) maculata were obtained during a 12-month trap-nesting program in a semideciduous forest reserve in southeastern Brazil. Trap nests were bamboo culms wider than those usually used in trap-nesting studies and it is suggested that species of Moureapis may prefer to nest in wide cavities. Nest construction was concentrated in the warm rainy season, but M. benigna had a secondary peak of nesting activity in the mid dry season, suggesting it is a bivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
18
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
3
18
1
2
Order By: Relevance
“…In general, our observations on the nesting biology of M. maculata is in agreement with what is known for the few other studied species of Megachile (Moureapis ) (e.g., Buschini et al 2009;Sabino and Antonini 2011;Cardoso and Silveira 2012) and described (Krombein 1967) for other leafcutter bee species (e.g., Laroca et al 1987;Zillikens and Steiner 2004;Torretta et al 2012). Specifically, all these studies reported the use of pre-existing cavities, a layer of overlapped pieces of leaves covering the entire chamber and an inner layer of pieces of leaves with the bottom of the brood cells formed by bending leaf pieces upwards from the base of the brood cells (Medler 1965;Kim 1992).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In general, our observations on the nesting biology of M. maculata is in agreement with what is known for the few other studied species of Megachile (Moureapis ) (e.g., Buschini et al 2009;Sabino and Antonini 2011;Cardoso and Silveira 2012) and described (Krombein 1967) for other leafcutter bee species (e.g., Laroca et al 1987;Zillikens and Steiner 2004;Torretta et al 2012). Specifically, all these studies reported the use of pre-existing cavities, a layer of overlapped pieces of leaves covering the entire chamber and an inner layer of pieces of leaves with the bottom of the brood cells formed by bending leaf pieces upwards from the base of the brood cells (Medler 1965;Kim 1992).…”
Section: Discussionsupporting
confidence: 91%
“…The male-biased sex ratio we found differed from that observed by Filho and Garófalo (2016) for Megachile (Crysosauros ) guaranitica and by Cardoso and Silveira (2012) for M. benigna , but was similar to the male-biased ratio found by Cardoso and Silveira (2012) for M. guaranitica . However, Megachile sex ratios can exhibit considerable intraspecific variation, as reported by Teixeira et al (2011), who found a male-biased ratio for M. benigna , whereas Cardoso and Silveira (2012) observed a slightly female-biased ratio for the same species.…”
Section: Discussioncontrasting
confidence: 61%
See 3 more Smart Citations